Relationship Between Teacher Education Programs and Motivation of Future Teachers to Pursue Teaching Careers (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Given the importance of this topic for teacher supply, quality, and retention, studying how teacher education programs influence prospective teachers' desire to become teachers has become an urgent matter in the field of educational research. This research investigates the ways in which the institutional atmosphere, practicum experiences, mentorship assistance, pedagogical training, and curriculum design all play a role in shaping the professional motivation of future teachers. Intrinsic drive, professional dedication, and long-term career goals are all greatly improved by organized programs that combine practical experience, introspective thinking, and positive mentor-mentee relationships. On the other side, trainees may be less motivated and more likely to leave a program if they do not have enough hands-on experience, constructive criticism, or supportive learning settings. Teachers' self-assurance, sense of professional identity, and faith in their own abilities as educators are all bolstered by the many ways in which teacher preparation programs contribute to these outcomes. To guarantee that today's classrooms are staffed by enthusiastic, knowledgeable, and dedicated teachers who can adapt to students' ever-changing needs, the results highlight the need of ongoing research into and development of better teacher preparation models.